Mobile deployment of stable diffusion models - Tran, Que An (Nanyang Technological University, 2024)
The rapid development of Generative Artificial Intelligence (Gen AI) in recent years has posed significant challenges in terms of both cost and power consumption since training and inference processes require intensive GPU computation. Moreover, the use of GPUs in cloud-based platforms for Gen AI inference raises privacy concerns such as the potential leakage of user prompts to external service providers, which might lead to legal complications afterwards.